2012
DOI: 10.1073/pnas.1120950109
|View full text |Cite
|
Sign up to set email alerts
|

Nanodiamonds and wildfire evidence in the Usselo horizon postdate the Allerød-Younger Dryas boundary

Abstract: The controversial Younger Dryas impact hypothesis suggests that at the onset of the Younger Dryas an extraterrestrial impact over North America caused a global catastrophe. The main evidence for this impact-after the other markers proved to be neither reproducible nor consistent with an impact-is the alleged occurrence of several nanodiamond polymorphs, including the proposed presence of lonsdaleite, a shock polymorph of diamond. We examined the Usselo soil horizon at Geldrop-Aalsterhut (The Netherlands), whic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
66
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 42 publications
(70 citation statements)
references
References 56 publications
(95 reference statements)
4
66
0
Order By: Relevance
“…Daulton (2012) also questioned the identification of lonsdaleite (hexagonal diamond), suggesting that some particles exhibited in Kennett et al (2009b) appear to be graphene-graphane aggregates. Van Hoesel et al (2012), Madden et al (2012), andBement et al (2014) also reported finding graphenegraphane clusters with diffraction patterns similar to those of lonsdaleite. Boslough et al (2012) suggested that some of the reported lonsdaleite from Lake Cuitzeo might instead be other minerals.…”
Section: Introductionmentioning
confidence: 95%
See 4 more Smart Citations
“…Daulton (2012) also questioned the identification of lonsdaleite (hexagonal diamond), suggesting that some particles exhibited in Kennett et al (2009b) appear to be graphene-graphane aggregates. Van Hoesel et al (2012), Madden et al (2012), andBement et al (2014) also reported finding graphenegraphane clusters with diffraction patterns similar to those of lonsdaleite. Boslough et al (2012) suggested that some of the reported lonsdaleite from Lake Cuitzeo might instead be other minerals.…”
Section: Introductionmentioning
confidence: 95%
“…Although the extraction process remains difficult, exacting, and laborintensive, we have successfully extracted NDs from hundreds of samples in or adjacent to the YDB layer on three continents and in the Greenland Ice Sheet, along with samples from the K-Pg impact, Sudbury Crater, and the Tunguska airburst. Six independent groups have successfully used this protocol or a version of it (Baker et al 2008;Demitroff et al 2009;Redmond and Tankersley 2011;Tian et al 2011;van Hoesel et al 2012;Bement et al 2014).…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations